Application of Canadian Experience for Supply Chain Strategy and Territorial Organization of Tourist Information Centres in the Regions of Russia - Vladimir A. Rubtsov; Aleksandr I. Zyrianov; Inna S. Zyrianova; Viktoria V. Danilevich (International Journal of Supply Chain Management, 2019)
One of the countries that have a common and long-running TIC network is Canada. The experience of this large northern country in the formation of regional information visit-service systems is of interest to Russia, since the countries in their characteristics are similar in size, distances, and natural conditions based on the supply chain strategy. Consider the TIC systems in the four Atlantic Canadian provinces. Tourist Information Centres are a new branch of services and a significant component of tourism management in many countries. In Russia, tourist information centres (TIC) are organized mainly in the largest cities of the regions and at the main sites visited. The experience of countries that are close in terms of geographic conditions and advanced in relation to the tourist infrastructure is important for the Russian regions. The study of the territorial organization of the Visitor Centres in the Atlantic Canada allows us to determine some geographical patterns. They will be taken into account when developing the system of tourist information centres in the Permsky Krai, one of the internal regions of Russia, which begin to form a high-level tourist infrastructure.